Ibero–American Consensus on Low- and No-Calorie Sweeteners: Safety, Nutritional Aspects and Benefits in Food and Beverages - Serra Majem, Lluis; Raposo, António; Aranceta Bartrina, Javier; Varela Moreiras, Gregorio; Logue, Caomhan; Laviada Molina, Hugo A.; Socolovsky, Susana; Pérez Rodrigo, Carmen; Aldrete Velasco, Jorge; Meneses Sierra, Eduardo; López García, Rebeca; Ortiz Andrellucchi, Adriana; et al. (Molecular Diversity Preservation International, 2018)
Abstract: International scientiﬁc experts in food, nutrition, dietetics, endocrinology, physical activity, paediatrics, nursing, toxicology and public health met in Lisbon on 2–4 July 2017 to develop a Consensus on the use of low- and no-calorie sweeteners (LNCS) as substitutes for sugars and other caloric sweeteners. LNCS are food additives that are broadly used as sugar substitutes to sweeten foods and beverages with the addition of fewer or no calories. They are also used in medicines, health-care products, such as toothpaste, and food supplements. The goal of this Consensus was to provide a useful, evidence-based, point of reference to assist in efforts to reduce free sugars consumption in line with current international public health recommendations. Participating experts in the Lisbon Consensus analysed and evaluated the evidence in relation to the role of LNCS in food safety, their regulation and the nutritional and dietary aspects of their use in foods and beverages. The conclusions of this Consensus were: (1) LNCS are some of the most extensively evaluated dietary constituents, and their safety has been reviewed and conﬁrmed by regulatory bodies globally including the World Health Organisation, the US Food and Drug Administration and the European Food Safety Authority; (2) Consumer education, which is based on the most robust scientiﬁc evidence and regulatory processes, on the use of products containing LNCS should be strengthened in a comprehensive and objective way; (3) The use of LNCS in weight reduction programmes that involve replacing caloric sweeteners with LNCS in the context of structured diet plans may favour sustainable weight reduction. Furthermore, their use in diabetes management programmes may contribute to a better glycaemic control in patients, albeit with modest results. LNCS also provide dental health beneﬁts when used in place of free sugars; (4) It is proposed that foods and beverages with LNCS could be included in dietary guidelines as alternative options to products sweetened with free sugars; (5) Continued education of health professionals is required, since they are a key source of information on issues related to food and health for both the general population and patients. With this in mind, the publication of position statements and consensus documents in the academic literature are extremely desirable. Keywords: non-nutritive sweeteners; low-calorie sweeteners; sweeteners; Ibero-American; safety; regulation; obesity; diabetes; cancer; added sugars